2023
DOI: 10.3390/w15061237
|View full text |Cite
|
Sign up to set email alerts
|

Defining Heat in Place for the Discovered Geothermal Brine Reservoirs in the Croatian Part of Pannonian Basin

Abstract: One of the important sources of renewable energy is geothermal heat. Its special feature of being independent 24/7 ensures the stability and security of the system, either for electricity or heat production. Geothermal energy has a local character and is limited by the geological characteristics of each state. In the Republic of Croatia, the development of geothermal energy is closely related to the development of the oil industry, as geothermal deposits were discovered during oil and gas exploration. Consider… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 39 publications
0
1
0
Order By: Relevance
“…Geothermal brine fluids offer potential in this regard, as several studies have demonstrated their ability to extract valuable minerals while minimising negative environmental impacts [9,10]. Utilising geothermal brine fluids for mineral extraction could provide a more sustainable and environmentally friendly alternative to traditional mining practices [11].…”
Section: Introductionmentioning
confidence: 99%
“…Geothermal brine fluids offer potential in this regard, as several studies have demonstrated their ability to extract valuable minerals while minimising negative environmental impacts [9,10]. Utilising geothermal brine fluids for mineral extraction could provide a more sustainable and environmentally friendly alternative to traditional mining practices [11].…”
Section: Introductionmentioning
confidence: 99%